Identification of Novel Type Three Secretion System (T3SS) Inhibitors by Computational Methods and Anti-Salmonella Evaluations - Yonghui Wang; Meihui Hou; Zhaodong Kan; Guanghui Zhang; Yunxia Li; Lei Zhou; Changfa Wang (Frontiers Media S.A., 2021)
Three type III secretion system (T3SS) inhibitors (compounds 5, 19, and 32) were identified by virtual screening and biological evaluation. These three compounds were evaluated against a panel of Salmonella species strains including S. enteritidis, S. typhi, S. typhimurium, S. paratyphi, and S. abortus equi, and their minimum inhibitory concentrations ranged from 1 to 53 μg/ml. Especially, these compounds showed comparable activity as the of the positive control gatifloxacin towards S. abortus equi. The present results suggest that these new T3SS inhibitors could be used as a potential lead molecule for drug development of anti-Salmonella.